Bacteriological and hydrogeochemical investigation of surface water and groundwater in Ikare- Akoko, Nigeria - Ogunribido, Tolulope (International Journal of Advanced Geosciences, 2017)
Ikare Akoko is underlain by the Pre - Cambrian Basement Complex rocks of Southwestern Nigeria and is about 6 kilometers away from Akungba Akoko that host Adekunle Ajasin University. The present study is to assess the quality of natural water for drinking and domestic purposes; perhaps they are susceptible to pollution due to increasing population. Fifteen water samples were collected from both surface water and groundwater during the onset of the dry season for physico – chemical and bacteriological analysis at the Central Research laboratory of Adekunle Ajasin University, Akungba – Akoko. The results indicate low pH, low total dissolved solids and low suspended solids. The concentration of total iron, sodium, calcium, magnesium, potassium, sulphate, bicarbonate and chloride are within the limit of WHO drinking water standard. Lead in most of the samples was below the detection limit but not higher than 0.1mg/L and also within the WHO limit of 0.3 mg/L. The bacteriological constituents of the water samples range between 15 and 30 cfu/ ml indicating bacterial contamination and sources may be due to water contact with cesspits or septic tanks. Therefore water in the study area requires microbial disinfection to upgrade its quality for drinking purposes. Piper’s diagram revealed that the hydrogeochemical evolution of water samples in this study area is Ca –HCO3- , this water have some salinity. Gibb’s diagram showed that the concentration of the dissolved chemical constituents were as a result of dissolution of host rock minerals due to water – rock interaction.